Security as the Determinant of Intention to Reuse Royal Plaza Surabaya Motor Parking - Isnaini, Nur (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research explores the critical nexus between security perceptions, user satisfaction, and reuse intentions in the context of motorbike parking at Royal Plaza Surabaya. This qualitative research explores security aspects in the reuse of the Royal Plaza Surabaya motorbike parking area. It involves observation, and document analysis methods. User perceptions of security, encompassing factors such as lighting, the presence of security officers, and surveillance systems, are identified as influential determinants of confidence in parking safety. Utilizing an innovative parking system aligned with principles of convenience, speed, and safety, the study investigates the impact of security measures on users' intentions to reuse the facility. The theoretical framework incorporates the Crime Prevention Through Environmental Design (CPTED) approach, emphasizing the significance of environmental design strategies in enhancing security perceptions. Findings reveal a theoretical relationship between security, user satisfaction, and reuse intentions. The active presence of security officers, extended beyond operating hours, and the integration of advanced technologies contribute to a well-maintained and secure parking environment. The theoretical implications underscore the multidimensional nature of security and its role in shaping user perceptions, extending discussions on environmental design, user satisfaction, and the interconnectedness of security measures. These findings provide valuable insights for managerial strategies, highlighting the importance of a comprehensive and effective security approach to foster user satisfaction and encourage repeat usage of parking facilities at Royal Plaza Surabaya.